An Opinion of Indian Manufacturing and Service Sector for Adopting Industry 4.0: A Survey - Dr. Jayant Kishor Purohit, Pratish Rawat, Dr. Yashpal, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Industry 4.0(I4.0) a German project can influence whole industrial and business system by digital transformation of product design, smart manufacturing and delivered to consumer. Industry 4.0(I4.0) project combines the physical world and digital world together through cyber physical systems and helps SMEs in enhancing production processes and increase productivity through emerging technologies such as Internet of Things and Services, Machine learning, Virtual Reality, cloud computing, business analytics etc. However, adoption and implementation of Industry 4.0 project is not an easy task due to existence of various challenges. In the present study, a survey is conducted with 40 Indian manufacturing and service organisations to get their opinion on Industry 4.0 and the level of adoption of in their organization. The objective of this research is to identify the general awareness and understanding of the concepts of Industry 4.0(I4.0) and its related emerging technologies along with their implementation levels in selected organizations. With the feedback received from the selected organizations, this paper analyzes the results and give some discussion.